Does the Economic Growth Improve Public Health? A Cross-Regional Heterogeneous Study in China - Niu, Xiao-Tong; Yang, You-Cai; Wang, Yu-Cong (Frontiers in Public Health, 2021)
On public health effect of economic growth in China is analyzed in this paper by using the panel threshold regression model. The empirical study shows that China's economic growth has a significant threshold effect on public health. After the threshold is exceeded, public health will be improved dramatically. The threshold effect is heterogeneous at the regional level. The Eastern region has no threshold, and both central and western regions have a single significant threshold. However, the threshold value and threshold effect in the central and western regions are also different. The heterogeneity is caused by the different levels of regional economic development. Therefore, based on public health utility maximization, the government should make different health policies according to the characteristics of regional development.